Analisis Hukum Peralihan Hak Milik Atas Tanah Melalui Hibah Untuk Anak di Bawah Umur (Studi Kasus: Permohonan Nomor 1284/Pdt.G/2021/PA.Bpp) - Yearta Kurnia Zalifah; Uzie Valerie; Aqila Aulia Rachma (Journal of Innovative and Creativity, 2025)
Granting land ownership to minors through a donation (hibah) remains a common legal occurrence in Indonesia, yet it poses legal complexities due to the minor’s incapacity to act independently under the law. Indonesian legislation considers minors legally incapable of conducting or receiving legal transactions, including the transfer of land ownership. This research aims to examine the legal safeguards provided for minors receiving land grants and the legitimacy of such grants according to current legal frameworks. Using a normative legal approach supported by a case study of Decision Number 1284/Pdt.G/2021/PA.Bpp at the Balikpapan Religious Court, this study finds that land donations to minors are legally permissible if a court-appointed legal guardian is in place. The guardian acts on the child’s behalf in administrative matters such as name transfer at the National Land Agency (BPN). The existence of such legal guardianship ensures both the legality of the land transfer and the protection of the minor’s property rights. The study emphasizes the central role of guardianship and upholding the best interests of the child in all legal actions involving minors.